Medetnični odnosi in politika - Jesih, Boris (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
The author analyses the influence of certain political aspects upon the shaping of interethnic relations and ethnic identity, whereby he particularly highlights the minority status in Slovene political life, as well as its position in the shaping of interstate relations with Hungary together with possibilities and role in the performing of social functions.
Keywords: etnični odnosi; Madžari; mednarodni odnosi; narodne manjšine; politika; Prekmurje; Slovenija